Functional Insight of Nitric-Oxide Induced DUF Genes in Arabidopsis thaliana - Nabi, Rizwana Begum Syed; Tayade, Rupesh; Imran, Qari Muhammad; Hussain, Adil; Shahid, Muhammad; Yun, Byung-Wook (Frontiers in Plant Science, 2020)
Advances in next-generation sequencing technologies facilitate the study of plant molecular functions in detail and with precision. Plant genome and proteome databases are continually being updated with large transcriptomic or genomic datasets. With the ever-increasing amount of sequencing data, several thousands of genes or proteins in public databases remain uncharacterized, and their domain functions are largely unknown. Such proteins contain domains of unknown function (DUF). In the present study, we identified 235 upregulated and 205 downregulated DUF genes from the available RNA-Seq-based transcriptome profiling datasets of Arabidopsis leaves exposed to a nitric oxide donor, S-nitroso-L-cysteine (CysNO). In addition, we performed extensive in silico and biological experiments to determine the potential functions of AtDUF569, and to elucidate its role in plant growth, development, and defense. We validated the expression pattern of the most upregulated and the most downregulated DUF genes from the transcriptomic data. In addition, a loss-of AtDUF569 function mutant was evaluated for growth, development, and defense against biotic and abiotic stress. According to the results of the study, AtDUF569 negatively regulates biotic stress responses and differentially regulates plant growth under nitro-oxidative stress conditions.